DOP82 Corticosteroid-free remission of Ulcerative Colitis with filgotinib maintenance therapy: Post hoc analysis of the phase 2b/3 SELECTION study. (27th May 2021) - Loftus, E; Vermeire, S; Feagan, B; Yun, C; Hsieh, J; Liu, X; Zhao, S; Moerch, U; Sandborn, W J; Hibi, T
Abstract: Background: Filgotinib (FIL) is a once-daily, oral, preferential Janus kinase 1 inhibitor in development for the treatment of inflammatory bowel disease. FIL for the treatment of moderately to severely active ulcerative colitis (UC) was evaluated in the phase 2b/3 randomized, double-blind, placebo (PBO)-controlled SELECTION study (NCT02914522). Long-term use of corticosteroids (CS) is associated with significant side effects. The aim of this post hoc analysis was to assess the CS-sparing effects of FIL in the SELECTION study. Methods: Patients (18–75 years old) with moderately to severely active UC were randomized (2:2:1) to receive FIL 100 mg (n = 564), FIL 200 mg (n = 507) or PBO (n = 280) once daily orally for up to 11 weeks (induction study). At week 11, FIL induction responders were rerandomized 2:1 to continue their induction FIL dose or to receive PBO (maintenance study). CS use was kept stable up to week 14, at which point mandatory CS tapering occurred. CS could be resumed during the maintenance study; however, if the baseline CS dose was exceeded this was considered treatment failure. In this post hoc analysis, CS-free remission was defined as remission at week 58 (endoscopic subscore ≤ 1, rectal bleeding subscore = 0 and ≥ 1-point decrease in stool frequency subscore to achieve 0 or 1) without systemic or localized CS use that was indicated for UC in the previous 1, 3, 6 or 8 months. Results: The baseline characteristics of patients in the maintenance study were similar across treatment groups (Table 1). Of the 92 patients receiving CS at maintenance baseline (week 11; maintenance week 0) who received FIL 200 mg during the maintenance study, 25 (27%) were in remission at week 58 and had been continuously CS-free for at least the previous 6 months (Table 2). The proportion of CS-free remitters in the FIL 200 mg group was consistently higher than with PBO (Table 2). In patients taking CS at maintenance baseline who had continued CS-use post baseline, lower median prednisone dosing was observed with FIL 200 mg than with PBO throughout the maintenance study (maximum difference at week 34 [maintenance week 23]: 5.0 mg vs 13.8 mg) (Figure 1). In SELECTION, a total of 199 patients received FIL 200 mg in the maintenance study, of whom 74 (37.2%) were in remission at week 58; of these 74 patients, 69 (93.2%) were continuously CS-free for at least the previous 6 months (Figure 2). Conclusion: In this post hoc analysis of SELECTION maintenance study data, FIL 200 mg was effective in reducing and eliminating CS use through to week 58 in patients with moderately to severely active UC. The vast majority of patients taking FIL 200 mg who were in remission at week 58 had not taken CS in the previous 6 months.